PENGARUH CUSTOMER REVIEW DAN CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN - Elnia Mei Wira; Mimi Kurnia Nengsih (UM. Bengkulu, 2026)
This study aims to analyze the influence of Customer Reviews and Customer Ratings on the purchase decisions of women’s clothing at Juragan Mode Bengkulu. The research method used is quantitative, employing data collection through questionnaires distributed to 90 respondents who are consumers of Juragan Mode Bengkulu. Data analysis was conducted using multiple linear regression to test the impact of the two independent variables on the dependent variable. The results show that both customer reviews and customer ratings have a significant effect on purchase decisions. The coefficient of determination (R²) of 98.5% indicates that the variables Customer Review and Customer Rating can explain the majority of the variation in consumer purchase decisions. These findings provide important implications for Juragan Mode management to optimize digital marketing strategies through improvements in the quality of customer reviews and ratings to increase sales. Keywords: Customer Review, Customer Rating, Purchase Decision, Women’s Clothing, Juragan Mode Bengkulu.